Ras oncogenes polymorphism in Turkish thyroid cancer patients - Öztürk, Fatma; Daloğlu, Cihan; Açık, Leyla; Kılıç, Mehmet; Koç, Mahmut (İstanbul Kültür Üniversitesi, 2008)
Molecula r mutations to proto - oncogene sequences may be involved in the pathogenesis of human thyroid neoplasm. Problems on oncogenes and tumor supressor genes activation in cell circle could cause tumor. Many oncogenes and tumor suppressing genes exist in varying percentages in various types of thyroid cancers. Ras, Gsp, Ret or Trk oncogenes can be involve in thyroid tumors . Members of t h e Ras gene family (H-ras, K-ras, and N-ras) are signal transferring proteins. These genes codes for 21 kDa GTP binding proteins. We studied 24 thyroid cancer and 77 control for ras gene point mutations in two different codons (12 and 13) using a restriction fragment length polymorphism technique. According to enzyme digesting, no c-K-ras gene codon 12/13 and N-ras gene codon 12 point mutation were observed in any of the samples we studied .
Keywords: ras gene; thyroid cancer; mutation; RFLP